Antitussive Effect of the GABA-Agonist Baclofen - Dicpinigaitis, Peter V.; Dobkin, Jay B. (Chest, 1997)
γ-Aminobutyric acid (GABA) is a central inhibitory neurotransmitter that also exists in peripheral tissues, including the lung. The GABA-agonist baclofen has been shown, in animal studies, to inhibit cough via a central mechanism, but has not been investigated in humans (to our knowledge). To evaluate the antitussive effect of baclofen in normal human subjects. Randomized, double-blind, placebo-controlled study. Academic medical center. Twenty healthy, adult volunteers. Subjects underwent cough challenge with inhaled capsaicin before and after a 14-day course of baclofen, 10 mg three times daily, or placebo. Capsaicin cough threshold (C5) was defined as the concentration of inhaled capsaicin inducing five or more coughs. Subjects receiving baclofen (n=10) demonstrated a significant elevation of capsaicin cough threshold compared with placebo subjects (n=10). Mean Δlog C5 after treatment was 0.48±0.19 (SEM) for the baclofen group, and −0.06±0.12 for the placebo group (p=0.024). Six of 10 subjects receiving baclofen, but none of the 10 subjects receiving placebo, demonstrated a fourfold or greater increase in capsaicin cough threshold (p=0.0054). The antitussive activity of low-dose, oral baclofen demonstrated in this study supports further investigation of this drug, or other GABA-agonists, for a potential therapeutic role in the treatment of pathologic cough.